2004
DOI: 10.1111/j.1464-410x.2004.05265.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral percutaneous nephrolithotomy in children

Abstract: In the paediatric section, two papers relating to the upper urinary tract are presented. The first, from Hungary, describes simultaneous bilateral percutaneous nephrolithotomy in 13 patients, where it was deemed feasible; this is the first such report. Authors from London report on unilateral nephrectomy in patients with nephrogenic hypertension, and found that it was successful in normalising blood pressure in patients with renal hypertension with a normal contralateral kidney. OBJECTIVE To evaluate the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 15 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…The results are equally good, with high patient satisfaction. A comparable series of children undergoing bilateral simultaneous PCNL was recently published by Salah et al [23]; they reported similar satisfactory outcomes, with the added benefit of decreased healthcare costs.…”
Section: Discussionmentioning
confidence: 53%
“…The results are equally good, with high patient satisfaction. A comparable series of children undergoing bilateral simultaneous PCNL was recently published by Salah et al [23]; they reported similar satisfactory outcomes, with the added benefit of decreased healthcare costs.…”
Section: Discussionmentioning
confidence: 53%
“…Reported complications of PCNL include postoperative fever (30%) and bleeding, the latter being the most reported complication associated with PCNL and consecutive transfusion rates ranging from 0% to 23.9% [37, 38, 4448]. The risk for blood transfusions is generally very low, with the report of one transfusion in 287 procedures in four pediatric studies [38, 44, 45, 47]. The highest reported number of transfusions needed (23.9%, or 16 out of 67) was by Zeren et al, which occurred mainly during their early PCNL procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The reports related with bilateral PCNL in children are scarce. Salah et al [12] first evaluated the results of 13 children (average age: 8 years) with bilateral kidney stones and reported the advantages of simultaneous bilateral PCNL as reduced psychological stress, one cystoscopy and anesthesia, less medication, and a shorter hospital stay and convalescence, with considerable savings in cost. The youngest patient in their study was 3 years old.…”
Section: Discussionmentioning
confidence: 98%